POLA DISTRIBUSI FOTOSINTAT PADA FASE VEGETATIF BEBERAPA VARIETAS KEDELAI PADA TANAH MASAM DI SULAWESI TENGGARA - SARAWA, SARAWA; ANAS, ARSY AYSYAH; ASRIDA, ASRIDA (Jurnal Agroteknos, 2014)
This study was to determine differences in the distribution of photosynthate of vegetative phase of several varieties of soybean (Glycine max L. Merril) cultivated on acid soil of Southeast Sulawesi. This research was conducted in the sub district Anduonohu, Poasia district and at Agrotechnology Laboratory, Faculty of Agriculture University Halu Oleo, Kendari from July to October 2013. The research design used was randomized block design (RBD) with three replications. Variety treatment consisted of varieties Kaba, Argomulyo, Tanggamus, Grobogan and Gema.  The variables observed in this study were root dry weight, stem dry weight, leaf dry weight, stem dry weight, and branch dry weight. Results of statistical analysis of the data showed that the treatment affected the distribution of photosynthate on different plant varieties. Different varieties gave significant effect on root dry weight, stem dry weight, leaf dry weight, branch dry weight.Keywords : Acid soils, distribution of photosynthate, soybean, varieties